2007
DOI: 10.1038/sj.onc.1210811
|View full text |Cite
|
Sign up to set email alerts
|

CD133+ HCC cancer stem cells confer chemoresistance by preferential expression of the Akt/PKB survival pathway

Abstract: The recent discovery of cancer stem cells (CSCs) has played a pivotal role in changing our view of carcinogenesis and chemotherapy. Based on this concept, CSCs are responsible for the formation and growth of neoplastic tissue and are naturally resistant to chemotherapy, explaining why traditional chemotherapies can initially shrink a tumor but fails to eradicate it in full, allowing eventual recurrence. Recently, we identified a CSC population in hepatocellular carcinoma (HCC) characterized by their CD133 phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
533
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(575 citation statements)
references
References 29 publications
34
533
1
1
Order By: Relevance
“…5A-D). These data were consistent with previous reports indicating that the Akt/ABCG2 pathway contributes to chemotherapeutic resistance (13,30). As a tightly binding competitive inhibitor, tunicamycin inhibits NLG by inhibiting the DPAGT1-catalyzed transfer of GlcNAc-1-P from UDPGlcNAc to dolichyl-P.…”
Section: Tunicamycin Sensitized Cells To Cddp Partially Through the Dsupporting
confidence: 82%
“…5A-D). These data were consistent with previous reports indicating that the Akt/ABCG2 pathway contributes to chemotherapeutic resistance (13,30). As a tightly binding competitive inhibitor, tunicamycin inhibits NLG by inhibiting the DPAGT1-catalyzed transfer of GlcNAc-1-P from UDPGlcNAc to dolichyl-P.…”
Section: Tunicamycin Sensitized Cells To Cddp Partially Through the Dsupporting
confidence: 82%
“…Our work (10,11), along with the work of other research groups (8,9), suggests that human HCC is very likely to be also hierarchically organized and originates from a primitive stem/progenitor group of cells for which CD133 + precursors constitute one of the most immature stage. Results from our previous studies were mainly derived from experiments done on HCC cell lines or xenograft tumors where CD133 expression was as high as 48% to 65% (It was recently observed that HCC cell lines Huh7 and PLC8024 express varying levels of CD133 expression, ranging from 48% to 60% for PLC8024 and from 49% to 65% for Huh7.…”
Section: Discussionmentioning
confidence: 97%
“…CD133 expression is found to represent only a minority of the tumor cell population in human HCC specimens (8)(9)(10). In addition, CD133 + cells are also more resistant to conventional chemotherapeutic drugs such as doxorubicin and 5-fluorouracil, the underlying mechanism of which required the preferential activation of the Akt/protein kinase B and Bcl-2 survival pathways (11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Akt pathway can be a target for novel antineoplastic therapies. 13 Furthermore, CD133 stem cell may pose as target for antibody-based therapies that would selectively eliminate these cells. 9 In conclusion, our study showed that CD133 þ cancer stem cell expression in childhood malignant melanoma might correlate with lymph node and/or visceral metastasis.…”
Section: Discussionmentioning
confidence: 99%